Seroprevalence of Cytomegalo Virus (CMV) among pregnant women in Thika, Kenya - Maingi, Zakayo (BMC Res Notes, 2014)
BACKGROUND: The fetal consequences of CMV infection have made it one of the most serious infections contracted during pregnancy. Despite the posed teratogenic risk during pregnancy, there is no national screening test for CMV infection is available during pregnancy in Kenya. Thus little is known on its epidemiological data that is necessary for health planners and care providers. METHODS: A cross sectional study was conducted at Thika district level 5 hospital, Kenya to investigate seroprevalence of CMV infections and associated possible risk factors among pregnant women. Structured questionnaires were used to gather socio-demographic data and ELISA was used to detect CMV infections using IgG and IgM. RESULTS: Out of 260 pregnant women, 201 (77.3%) were CMV IgG 21(8.1%) CMV IgM being on acute stage of the disease. Marital status (OR = 3.7533, 95% CI =3.0231-6.9631, P < 0.0001), parity (OR = 3.7533, 95% CI = 3.0231-6.9631, P < 0.0001), and education (OR = 3.7533, 95% CI = 3.0231-6.9631, P < 0.0001), history of blood transfusion (OR = 0.0374, 95% CI = 0.00120-0.1168, OR = 0.3804) were found to significantly influence seropostivity in univariate analysis. CONCLUSION: The 88.4% CMV prevalence rate being detected among pregnant women calls for vaccine and routine screening for CMV infections and its associated risk factors in this kind of settings.